Women in Twentieth-Century Britain : Social, Cultural and Political Change - Zweigiger-Bargielowska, Ina (Routledge, Taylor and Francis, 2014)
Women's lives have changed dramatically over the course of the twentieth century: reduced fertility and the removal of formal barriers to their participation in education, work and public life are just some examples. At the same time, women are under-represented in many areas, are paid significantly less than men, continue to experience domestic violence and to bear the larger part of the burden in the domestic division of labour. Women in 2000 may have many more choices and opportunities than they had a hundred years ago, but genuine equality between men and women remains elusive. This unique.